2017
DOI: 10.1093/jnci/djw329
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survival of BRCA1/BRCA2 Mutation Carriers in a Hospital-Based Cohort of Young Women

Abstract: BRCA1/2 mutation carriers diagnosed with breast cancer before age 50 years are prone to a worse survival, which is partly explained by differences in tumor characteristics, treatment response, and second ovarian cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 44 publications
4
52
0
3
Order By: Relevance
“…In our study, we screened all coding regions and exon–intron boundaries of BRCA1/2 and PALB2 genes in 2769 unselected Chinese women with breast cancer using next‐generation sequencing assays. The findings of our study showed that the overall prevalence of BRCA1 and BRCA2 mutations was 5.4%, which is similar to those reported in unselected patients in China (5.3%) and Malaysia (6.0%) recently . However, this prevalence is lowered than that detected in the unselected Ashkenazi Jewish population (mutation rates range from10.3 to 12%) …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, we screened all coding regions and exon–intron boundaries of BRCA1/2 and PALB2 genes in 2769 unselected Chinese women with breast cancer using next‐generation sequencing assays. The findings of our study showed that the overall prevalence of BRCA1 and BRCA2 mutations was 5.4%, which is similar to those reported in unselected patients in China (5.3%) and Malaysia (6.0%) recently . However, this prevalence is lowered than that detected in the unselected Ashkenazi Jewish population (mutation rates range from10.3 to 12%) …”
Section: Discussionsupporting
confidence: 84%
“…However, whether the germline mutations in BRCA1/2 or in PALB2 genes have independent prognostic influence on breast cancer patients remains unclear. Some previous studies reported that BRCA1/2 mutation carriers had a better survival outcome when compared to control groups, while other studies suggested that the prognosis was worse or no different, and most of them were based on patients with breast cancer selected for family history or age at diagnosis. More importantly, to date, few studies have estimated the survival rate in women with a PALB2 mutation and breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Our results were in broad agreement with more recent studies, although others had reported conflicting results. [27][28][29][30][31][32] The percentage of BRCA-associated patients in our study (12.6%) was similar to a prior prospective cohort study, 33 The bold values derived from univariated analysis indicate that BRCA-mutation status and menopausal status might attribute to risk of contralateral breast cancer (CBC), however, only BRCA-mutation status confer to the independent risk factor of CBC.…”
Section: Discussionsupporting
confidence: 85%
“…Published studies and meta-analyses have reported better, worse, and similar outcomes for patients with a BRCA1 or BRCA2 mutation compared with patients with sporadic breast cancer. 8 , 9 , 10 , 11 , 12 , 13 , 14 A comprehensive meta-analysis of 66 studies of breast cancer survival in patients with a BRCA1 or BRCA2 mutation compared with non-carrier patients or the general breast cancer population, which assessed study quality as well as outcome data, concluded that “it is not yet possible to draw evidence based conclusions about the association between BRCA1 [or] BRCA2 mutation carriership and breast cancer prognosis”. 12 We undertook the Prospective Outcomes in Sporadic versus Hereditary breast cancer (POSH) study, the primary aim of which was to determine the effect of inherited BRCA1 or BRCA2 mutations on outcomes in patients with young-onset breast cancer.…”
Section: Introductionmentioning
confidence: 99%